Aplikasi Teknik Double Wash unutk Isolasi DNA Spesies pada Sampel Cangkang Kapsul Lunak: Application of Double Wash Technique for Species DNA Isolation in Soft Capsule Shell Samples - Marcella Sutanta; Diana Tri Wulan; Yusrina Nabila; Alfi Sophian (Eruditio : Indonesia Journal of Food and Drug Safety, 2021)
The presence of gelatin components can be identified through fat, protein and DNA. DNA can be obtained through the DNA isolation process which is the process of separating DNA from other components of the cell. The DNA purification stage is the most important thing in DNA isolation because at this stage it can reduce to a minimum the number of contaminants in DNA isolates to determine the purity and concentration of the DNA isolate obtained. The purpose of this technique is to produce DNA isolates that are low inhibitors or are in the purity range of 1.7-2.1. The extraction method used in this study used the double wash technique, the technique was modified from the test stage following the manual kit used, it's just that the technique used was modified at the washing stage with each washing done twice in the washing section. first and second washing so that a total of four items of washing were carried out. The results of the DNA isolates were then analyzed for the purity and concentration of DNA obtained using a nanophotometer, the DNA isolates obtained were in the range of 4,400 - 5,500 ng/µL with an average of 4,950 ng/µL. As for the purity value measured at the wavelength A260/A280, the results were obtained with a purity range between 1,760 - 1,840 with an average of 1,800. This research concludes that all the extracted samples show the results of DNA isolates that fall into the category of good DNA and meet the requirements needed in molecular analysis.